2021
DOI: 10.1016/j.tranon.2020.100964
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of adding bevacizumab in neoadjuvant therapy for locally advanced rectal cancer patients: A systematic review and meta-analysis

Abstract: Background Patients with locally advanced rectal cancer (LARC) are more likely to suffer local recurrence and distant metastases, contributing to worse prognoses. Considering the provided dramatic reduction of local recurrences, neoadjuvant CRT (nCRT) followed by curative resection with total mesorectal excision (TME) and adjuvant chemotherapy has been established as standard therapy for LARC patients. However, the efficacy of adding bevacizumab in neoadjuvant therapy, especially in induction ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
6
1
Order By: Relevance
“…23 On the other hand, several studies have shown controversial results regarding whether CapeOX plus radiation and monoclonal antibody could lead to a better survival without more adverse events. [24][25][26] In this study, no statistically significant difference in pCR (6.25% vs 8.33%, P = 1.000) or ORR (50.00% vs 58.33%, P = 0.682) was noted between CapeOX and mFOLFOX6. Interestingly, although the treatment duration was shorter for four-cycle mFOLFOX6 compared with four-cycle CapeOX (2 months vs 3 months), mFOLFOX6 achieved better TRG compared with CapeOX.…”
Section: Discussioncontrasting
confidence: 49%
“…23 On the other hand, several studies have shown controversial results regarding whether CapeOX plus radiation and monoclonal antibody could lead to a better survival without more adverse events. [24][25][26] In this study, no statistically significant difference in pCR (6.25% vs 8.33%, P = 1.000) or ORR (50.00% vs 58.33%, P = 0.682) was noted between CapeOX and mFOLFOX6. Interestingly, although the treatment duration was shorter for four-cycle mFOLFOX6 compared with four-cycle CapeOX (2 months vs 3 months), mFOLFOX6 achieved better TRG compared with CapeOX.…”
Section: Discussioncontrasting
confidence: 49%
“…Finally, it was confirmed that the neoadjuvant treatment of NAC plus bevacizumab has good safety and the patient's survival conditions are also ideal. Another meta-analysis also reached a similar conclusion, supporting that the addition of bevacizumab in NAC has ideal safety while improving the efficacy [ 18 ]. In summary, adding bevacizumab to NAC may be a safe and feasible preoperative option for neoadjuvant therapy in LARC.…”
Section: Introductionmentioning
confidence: 67%
“…A recent meta-analysis showed that the pooled pCR rate for TNT-relevant cohorts of LARC patients was 33%. 76 Another recent meta-analysis of randomized trials of LARC by Riesco-Martinez et al 77 showed that compared with standard nCRT, TNT significantly improved pCR rate (13.3% vs. 23.5%, p < 0.001), the 3-year DFS, and the 3-year OS, although the rates of G3/4 AEs and R0 resection were not significantly different. Kasi et al 78 79 showed that TNT compared with standard nCRT did not increase 30-day postoperative mortality (p = 1.0), re-admissions (p = 0.82), or length of hospital stay.…”
Section: Future Directions In Tntmentioning
confidence: 98%
“…showed that LARC patients who received TNT followed by surgery had a 5‐year OS of 74.4%, a 5‐year DFS of 65.4%, a weighted mean LR of 3.5% (range 0%–7%), and a DM rate of 20.6% (range 5%–31%). A recent meta‐analysis showed that the pooled pCR rate for TNT‐relevant cohorts of LARC patients was 33% 76 . Another recent meta‐analysis of randomized trials of LARC by Riesco‐Martinez et al 77 .…”
Section: Future Directions In Tntmentioning
confidence: 99%